1989
DOI: 10.1159/000215884
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Heparin in Peritoneal Dialysis and Its Effect on Fibrinopeptide A in Plasma and Dialysate

Abstract: In 6 patients on continuous ambulatory peritoneal dialysis we investigated the inhibition of intraperitoneal fibrin formation by heparin. A continuous addition of 500 U of heparin per liter dialysate was used for 52 h. In plasma no heparin activity could be detected, even 52 h after intraperitoneal administration of heparin. The fibrin formation was determined by fibrinopeptide A, a thrombin-induced split product of fibrinogen. In patients under regular continuous ambulatory peritoneal dialysis we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…We have previously reported that the inhibition of factor Xa was unaffected by the intraperitoneal tinzaparin treatment [10]. Indeed, intraperitoneal heparins seem to have very limited effects on systemic haemostasis [18, 19]. It is of interest to note that the present study has demonstrated a pronounced local effect of intraperitoneal tinzaparin on both fibrinogen-fibrin turnover and inflammation, while the systemic effect was primarily linked to inflammation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We have previously reported that the inhibition of factor Xa was unaffected by the intraperitoneal tinzaparin treatment [10]. Indeed, intraperitoneal heparins seem to have very limited effects on systemic haemostasis [18, 19]. It is of interest to note that the present study has demonstrated a pronounced local effect of intraperitoneal tinzaparin on both fibrinogen-fibrin turnover and inflammation, while the systemic effect was primarily linked to inflammation.…”
Section: Discussionsupporting
confidence: 50%
“…It is of interest to note that the present study has demonstrated a pronounced local effect of intraperitoneal tinzaparin on both fibrinogen-fibrin turnover and inflammation, while the systemic effect was primarily linked to inflammation. As intraperitoneal fibrinogen-fibrin turnover is a local phenomenon [19], these observations imply that the systemic inflammatory response could have become reduced secondary to the reduced intraperitoneal inflammation, i.e. that the systemic inflammatory response is affected by the intraperitoneal inflammation in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…FPB p 15-42 and P-TG were all increased in CAPD patients compared with healthy individuals, while PT was shorter. In other studies [2,[21][22][23][24], FVII. TAT, protein S, fibrino gen. FPA.…”
Section: Discussionmentioning
confidence: 94%
“…Hypercoagulability and secondary hyperfibrinolysis have also been noted in CAPD patients [2,[20][21][22][23][24] although they do not require anticoagulants for extracor poreal circulation during dialysis and the mechanism involved is unclear. In recent years, it has become possible to measure many of the markers produced during coagu lation and fibrinolysis [4,5,25,26], In the present study, FIX.…”
Section: Discussionmentioning
confidence: 99%
“…The main risk of fibrin overproduction is catheter obstruction. Intraperitoneal injection of unfractionated heparin (500 IU/L of dialysate) can prevent intraperitoneal fibrin formation without significant systemic anticoagulant effect and is recommended by some nephrology centers as long as the dialysate appears cloudy …”
Section: Cloudy Dialysatementioning
confidence: 99%